Analisis Kualitas Aset Taman Kota Berdasarkan Neighbourhood Green Space Tool di Taman Abdi Negara Kota Bandung - Wida Oktavia Suciyani; Husna Candranurani Oktavia; Alshanda Ridarini (Jurnal Lanskap Indonesia, 2023)
One of the city parks owned by Bandung City is Taman Abdi Negara. The area of Taman Abdi Negara covers 4.1 ha. The condition of Taman Abdi Negara experienced various damages such as the absence of a parking area, damage to the paving blocks of the road surface for pedestrians, the absence of lighting in the garden area, the children'splay facilities were not maintained and left inoperative, the gazebo and seats were damaged, many acts of vandalism, as well as dirty conditions with scattered garbage and inadequate for visitors. This paper aims to analyze asset quality based on five criteria, i.e. access, recreation facilities, amenities, natural features, and incivilities. This study uses an exploratory method with data collection through observation and interviews with the manager of Taman Abdi Negara. The results obtained show that the asset quality of Taman Abdi Negara is based on the dimensions of adequate/medium quality access, while the dimensions of recreation facilities, amenities, natural features and incivilities are of poor quality. Thus, the overall asset quality of Taman Abdi Negara is included in the category of poor. This is due to the poor quality of assets in the park area, so it is necessary to plan for asset development and then carry out asset maintenance activities in Taman Abdi Negara, Bandung City.